Hubungan Persepsi Pola Asuh Orang Tua dan Karakteristik Siswa dengan Kecemasan Siswa Kelas 7 - 12 di Sekolah X Jakarta - Apryanti, Andi Rika; Hadi, Ella Nurlaella; Damayanti, Rita (UI Scholars Hub, 2025)
Background. Anxiety is a negative emotional response that is subjective with physical symptoms. Anxiety is influenced by various factors such as parenting styles and student characteristics. Objective. The purpose of this study was to determine the relationship between perceived parenting styles and student characteristics with anxiety in 7th – 12th grade students at School X Jakarta. Method. This research is a quantitative study using a cross-sectional design. Data from 220 of 486 students who were willing to take part of this study and had permission from their parents were collected by filling out a questionnaire independently. Data were analyzed using the chi-square test. Results. The results showed that the prevalence of anxiety in 7th – 12th grade students at School X Jakarta were 27.3%. The most dominate student’s perceptions of their parenting styles are authoritative (36.4%) and neglectful (36.4%). Meanwhile, the characteristics of the students were early teens (58.2%), female (50.5%), and junior high school level (72.7%). The results of the analysis showed a significant relationship between neglectful parenting, indulgent parenting, student gender, and grade level with student anxiety. Conclusion. Student at risk of experiencing anxiety are female, high school level, and parenting style is neglectful or indulgent. For this reason, School X needs to conduct an evaluation to these student, as well as providing a